Polarization Reconstruction Based on Monte Carlo Simulations for a Compton Polarimeter - Tobias Over-Winter; Wilko Middents; Günter Weber; Thomas Stöhlker (Atoms, 2025)
State-of-the-art 2D sensitive semiconductor detectors developed within the SPARC collaboration can be utilized as dedicated Compton polarimeters in the hard X-ray regime. We report on the technique of Compton polarimetry utilizing such a detector and present a method to determine the linear polarization of an analyzed hard X-ray beam by means of Monte-Carlo-simulated data sets.